The effect of Negro Pepper (Xylopia aethiopica fruit) extract on Prostaglandin E2 and connexin 43 levels in the early and mid-gestation period of pregnant Wistar rat - Gloria Nosariemen Azekhumen; Maureen Isoken Ebomoyi (Health and Biosciences, 2026)
Excessive prostaglandin E2 production and aberrant increase in connexion 43 level during pregnancy had been reported to lead to uterine contraction and consequently pregnancy loss. This study investigated the effect of negro pepper (NP) extract on prostaglandin E2 (PGE2) and connexion 43 (Cx 43) levels in pregnant Wistar rats. 40 virgin female Wistar rats weighing between 150g to 180g were purchased from the animal house of the Department of Anatomy, University of Benin. The dry fruits (NP) were ground to powder form and soaked with n-hexane using maceration method for 24 hrs and the resultant mixture was filtered with filter paper to obtain the filtrate which was evaporated to dryness using a rotary evaporator to obtain the oil. The female rats were mated with male rats to achieve pregnancy. The pregnant rats were grouped into two phases: Germinal phase and Embryonic Phase and each phase was divided into four groups (A. B, C and D) of n=5 rats each. The first three groups (A, B and C) in each phase served as test groups and were administered orally 0.25, 0.5 and 1ml/Kg b.wt of the hexane extract of XA fruit respectively while group D served as control in each phase of gestation. 24 hours after the last administration, the rats were sacrificed using chloroforms anaesthesia, and their uteri were excised and used for the biochemical analysis. In conclusion, NP extract significantly decreased PGE2 level across all doses while Cx43 level increased significantly at 0.5 and 1ml/kg b.wt of extract compared to control in the Germinal phase. However, PGE2 and Cx43 levels significantly increased at 0.5ml/kg and 1mg/kg b.wt. in the embryonic phase, showing that the extract exhibits a phase-dependent biochemical alteration which point towards the disrupted endometrial receptivity and accelerated myometrial contractility. Consequently, the consumption of hexane extract of NP should be strictly avoided due to its ability to trigger uterine contractions, which may result in pregnancy loss.